Historical trends and spatial distributions of polycyclic aromatic hydrocarbons in the upper reach of the Huai River, China: Evidence from the sedimentary record. (April 2019) - Feng, Jinglan; Liu, Menglin; Zhao, Jiahui; Hu, Pengtuan; Zhang, Fei; Sun, Jian-Hui
Abstract: The historical trends and spatial distributions of 15 polycyclic aromatic hydrocarbons (PAHs) in sediments from the upper reach of the Huai River were investigated. The concentrations of total PAHs (ΣPAHs) in the surface sediments varied from 3.96 to 379 ng/g (average: 65.3 ng/g). PAHs in the surface sediments of the studied area were at a low level compared with some other rivers around the world. The component characteristics showed that four-ring PAHs were predominant. The principal component analysis-multiple linear regression (PCA/MLR) showed that PAHs in the surface sediments primarily originated from coal combustion and vehicular emissions, which accounted for 62.7% and 37.3% of ΣPAHs, respectively. The concentration of ΣPAHs in the sediment core ranged from 2.31 to 21.9 ng/g with deposition flux ranging from 1.91 to 33.3 ng/cm 2 /year. The historical pattern of PAHs correlated with the Chinese socioeconomic conditions during 1912–2014, confirming that PAHs are a sensitive tracer for anthropogenic activity. Since the 1980s, there was a sharp increase in PAHs concentrations in the studied core. PCA/MLR showed that PAHs in the sediment core were mainly from the burning of fossil fuels. The concentration of PAHs in the surface sediment and sediment core was affected by the content of total organic carbon and black carbon. The result revealed in this study could serve as a reference for the development of relevant remedial strategies for the management of the Huai River. Highlights: Sediment core from the upper reach of the Huia River were analyzed for PAHs. One century deposition of PAHs was reconstructed. The depositional flux of PAH generally showed an increasing trend. Temporal profiles of PAHs reflected local economic conditions.